PENGARUH PENERAPAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN DAN LEVERAGE SEBAGAI VARIABEL KONTROL - Evelyn Setiawan; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This study aimed to prove whether the implication of corporate governance had influence on firm value with firm size and leverage as control variables. The implementation of corporate governance measured by using the Corporate Governance Perception Index (CGPI) rating scores compiled by The Indonesian Institute for Corporate Governance. Meanwhile, firm value measured by using Tobin’s Q. This study tested 93 companies that listed in the CGPI rating as well as in the Indonesia Stock Exchange during 2001-2015 with a total of 185 obesarvation data. The research result showed that the implementation of corporate governance had significant positive affect on firm value. The result also indicated that firm size had significant negative affect on firm value and leverage also had significant negative affect on firm value.